Perceived social support and emotional exhaustion in HIV/AIDS counselling (2014)
Counsellors have been identified as a group of professionals at elevated risk of burnout in general and emotional exhaustion in particular. Considering the nature of the illness, the multifaceted needs of the client, the relative paucity of available counsellors/counselling centers and various psychosocial issues connected with HIV/AIDS, the potential for emotional exhaustion is especially high among HIVIAIDS counsellors. Despite these problems, little or nothing is being done by way of rigorous research and ameliorative activities on this important issue. This study investigated emotional exhaustion among HIV/AIDS counsellors in Lagos State, Nigeria. Two hundred and forty purposively selected counsellors (170 females and 70 males with an average age of 34.19 years) participated in the cross-sectional survey. Results indicated that respondents were very high on emotional exhaustion. Results also indicated that counsellors who perceived high level of social support were indeed significantly lower on emotional exhaustion than those who perceived low social support as hypothesized, t (2, 238) = 4.67; <.05. Additionally, age, education and work experience significantly independently and jointly predicted emotional exhaustion {R=.50; F=26.01; P NS} by jointly accounting for about 25% of the variances in emotional exhaustion. Furthermore, significant influence of marital status on emotional exhaustion was found, (F(4,235)=7.83; P<.01). These findings were exhaustively discussed and recommendations were made, especially on the need for psychologists, researchers, practitioners, and other stakeholders to address emotional exhaustion among HIVIAIDS counsellors actively. This could improve both the lives of the concerned professionals and the quality of the services they provide.